1993
DOI: 10.1200/jco.1993.11.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis following salvage mastectomy for recurrence in the breast after conservative surgery and radiation therapy for early-stage breast cancer.

Abstract: We conclude that the histology of the recurrent tumor is an important prognostic factor for the risk of further relapse. Patients with purely noninvasive or focally invasive tumors have an excellent prognosis following salvage mastectomy. In contrast, patients with predominantly invasive tumors are at substantial risk for further relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
74
0
6

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(88 citation statements)
references
References 0 publications
8
74
0
6
Order By: Relevance
“…7,8 In a study from the Joint Center for Radiation Therapy performed in patients with noninvasive or focally invasive recurrent tumors, there were no chest wall recurrences observed at a median follow-up of 39 months. 8 In contrast, 7% of patients who presented with an invasive in-breast local recurrence developed a subsequent chest wall recurrence. In a series of patients from Sweden, chest wall recurrences occurred in 19% of 65 patients after mastectomy for local in-breast recurrence at a median follow-up of 13 years.…”
Section: Local Recurrence Risk After Mastectomy For In-breast Local Rmentioning
confidence: 99%
See 4 more Smart Citations
“…7,8 In a study from the Joint Center for Radiation Therapy performed in patients with noninvasive or focally invasive recurrent tumors, there were no chest wall recurrences observed at a median follow-up of 39 months. 8 In contrast, 7% of patients who presented with an invasive in-breast local recurrence developed a subsequent chest wall recurrence. In a series of patients from Sweden, chest wall recurrences occurred in 19% of 65 patients after mastectomy for local in-breast recurrence at a median follow-up of 13 years.…”
Section: Local Recurrence Risk After Mastectomy For In-breast Local Rmentioning
confidence: 99%
“…3,4,[6][7][8][9][10][11][12][13][14][15][16][17] These studies demonstrated that a second local recurrence in the form of a chest wall recurrence occurs in approximately 2-32% of patients. Thus, mastectomy after in-breast local recurrence does not necessarily eliminate the risk of subsequent secondary local recurrences at the chest wall.…”
Section: Local Recurrence Risk After Mastectomy For In-breast Local Rmentioning
confidence: 99%
See 3 more Smart Citations